Investigating the dynamics of granular flow - Longjas, Anthony G.
This thesis investigates the flow dynamics of granular materials. The first chapter incorporates thermodynamic formalism to a force - geometry model in describing the jamming behavior of homogeneous and mixed disks when poured into a two-dimensional hopper. The second chapter presents an experimental verification of a dissipative self-organized sandpile. Statistical characteristics of avalanches in rain- and vibration-driven granular mounds are examined wherein avalance size distributions are found to exhibit crossover from power-law to non-power-law as the driving rate is increased. The results are important since it provides justification for using scaled set-up in testing large sized events like landslides. The last chapter shows experimentally the frequency-size statistics and temporal evolution of cascading sand piles are found to be highly dependent on the initial driving rate of the system. Results of this thesis provide useful insights into the problem of jamming, avalanches and cascades of granular materials.
Computer print out.
Keywords: Granular materials